News Coverage of Gaza Events on the BBC Arabic Website: An Analytical Study Covering the Period from October 7, 2023, to February 6, 2024 - Hadi, Sabreen Noori; Hashim, Ahmed Hasan (ALBAHITH ALALAMI, 2025)
This study aims to answer the main question: What is the nature of the news coverage provided by the BBC Arabic website for Gaza events? It seeks to achieve several objectives, most notably: identifying the key themes in the news coverage, uncovering the methods used to report on Gaza events on the BBC Arabic site, and pinpointing the primary sources utilized in this coverage. Classified as descriptive research, this study employs a survey method and utilizes a content analysis tool to meet its objectives. The research yielded several findings, including the following: the military frame ranked first with a frequency of 678 occurrences and a percentage of (34.53%), while the humanitarian frame ranked second with 639 occurrences (32.55%). Regarding the style of reporting, “simple news coverage” attained the highest position with 116 occurrences (45.84%), whereas “narrative-driven news coverage” ranked second with 79 occurrences (31.22%). Concerning the sources of information, the “correspondent” category ranked first with 126 occurrences (49.80%), followed by “news agencies” with 51 occurrences (20.15%).